Study of Adhesive Wear of Epoxy Reinforced with glass fibers Composite Material - Abbas, Rula Abdul Khider; Sahib, Muzher Ali; Dyaa, Balkees Mohammed (Nahrain University College of Engineering Journal, 2010)
The dry wear, compression resistance and hardness of a material that consists of Epoxy reinforced with (25%) ratio of Glass fiber have been Studied. A comparison is made between the properties of the composite at temperature ( 20 2 0C) with those of un reinforced Epoxy to find out the effect of reinforcement on the composite. Volume fraction for specimen was (25%) and the reinforcement material were continuous fiber oriented in woven raven. The measurement of wear rate shows a decreases with reinforcement. Compression resistance and Hardness increase with reinforcement. The results of compaction have clearly shown that wear rate and wear rate volume increasing normal applied load, sliding distance, time sliding and hardness of disc. The results also show that wear rate and wear rate volume for all materials increases with normal applied load and running time. The results also show that wear rate and wear rate volume decrease with increasing the applied with increasing the hardness of disc and sliding distance. The topography of some physically tested was studied using optical microscopy